KESADARAN HUKUM MASYARAKAT DALAM PERLINDUNGAN KEKAYAAN INTELEKTUAL DI KOTA SUNGAI PENUH: FADLAN KALMA, S.Th.I., MH - fadlan kalma fadlan (JURNAL ADMINISTRASI NUSANTARA, 2018)
The problem that will be discussed in this paper is about how the community's legal awareness about the importance of legal protection of intellectual property rights in Sungai Penuh City. The research location was carried out in Sungai Penuh City using an empirical juridical approach and qualitative data analysis. Based on the results of the study it can be concluded that Sungai Penuh City has the potential of a very large Intellectual Property but has not yet received maximum IP protection.